Irrational would be the correct answer
Answer:
6: 12
7: 14
8: 16
Step-by-step explanation:
You do the last (y) term given [18] minus the first (y) term [10] given divided by how many terms it takes to get from the last (y) term given minus the first (y) term given [4]. So the equation looks like this:
(18 - 10)/4= 8/4 = 2
Answer:
-2
Step-by-step explanation:
X1 Y1 X2 Y2
(-15, 30) (7, -14)
Y2-Y1 = -14-30 = -44 = -2
———————————————
X2-X1 = 7-(-15)= 22 = 1
Answer:
![y=e^{\frac{-t}{2}}\left ( \cos\left ( \frac{\sqrt{3}t}{2} \right )+\frac{1}{\sqrt{3}}\sin \left ( \frac{\sqrt{3}t}{2} \right ) \right )](https://tex.z-dn.net/?f=y%3De%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%5Cleft%20%28%20%5Ccos%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%2B%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%5Csin%20%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%20%5Cright%20%29)
Step-by-step explanation:
A second order linear , homogeneous ordinary differential equation has form
.
Given: ![y''+y'+y=0](https://tex.z-dn.net/?f=y%27%27%2By%27%2By%3D0)
Let
be it's solution.
We get,
![\left ( r^2+r+1 \right )e^{rt}=0](https://tex.z-dn.net/?f=%5Cleft%20%28%20r%5E2%2Br%2B1%20%5Cright%20%29e%5E%7Brt%7D%3D0)
Since
, ![r^2+r+1=0](https://tex.z-dn.net/?f=r%5E2%2Br%2B1%3D0)
{ we know that for equation
, roots are of form
}
We get,
![y=\frac{-1\pm \sqrt{1^2-4}}{2}=\frac{-1\pm \sqrt{3}i}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B-1%5Cpm%20%5Csqrt%7B1%5E2-4%7D%7D%7B2%7D%3D%5Cfrac%7B-1%5Cpm%20%5Csqrt%7B3%7Di%7D%7B2%7D)
For two complex roots
, the general solution is of form ![y=e^{\alpha t}\left ( c_1\cos \beta t+c_2\sin \beta t \right )](https://tex.z-dn.net/?f=y%3De%5E%7B%5Calpha%20t%7D%5Cleft%20%28%20c_1%5Ccos%20%5Cbeta%20t%2Bc_2%5Csin%20%5Cbeta%20t%20%5Cright%20%29)
i.e ![y=e^{\frac{-t}{2}}\left ( c_1\cos\left ( \frac{\sqrt{3}t}{2} \right )+c_2\sin \left ( \frac{\sqrt{3}t}{2} \right ) \right )](https://tex.z-dn.net/?f=y%3De%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%5Cleft%20%28%20c_1%5Ccos%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%2Bc_2%5Csin%20%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%20%5Cright%20%29)
Applying conditions y(0)=1 on
, ![c_1=1](https://tex.z-dn.net/?f=c_1%3D1)
So, equation becomes ![y=e^{\frac{-t}{2}}\left ( \cos\left ( \frac{\sqrt{3}t}{2} \right )+c_2\sin \left ( \frac{\sqrt{3}t}{2} \right ) \right )](https://tex.z-dn.net/?f=y%3De%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%5Cleft%20%28%20%5Ccos%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%2Bc_2%5Csin%20%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%20%5Cright%20%29)
On differentiating with respect to t, we get
![y'=\frac{-1}{2}e^{\frac{-t}{2}}\left ( \cos\left ( \frac{\sqrt{3}t}{2} \right )+c_2\sin \left ( \frac{\sqrt{3}t}{2} \right ) \right )+e^{\frac{-t}{2}}\left ( \frac{-\sqrt{3}}{2} \sin \left ( \frac{\sqrt{3}t}{2} \right )+c_2\frac{\sqrt{3}}{2}\cos\left ( \frac{\sqrt{3}t}{2} \right )\right )](https://tex.z-dn.net/?f=y%27%3D%5Cfrac%7B-1%7D%7B2%7De%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%5Cleft%20%28%20%5Ccos%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%2Bc_2%5Csin%20%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%20%5Cright%20%29%2Be%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%5Cleft%20%28%20%5Cfrac%7B-%5Csqrt%7B3%7D%7D%7B2%7D%20%5Csin%20%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%2Bc_2%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7D%5Ccos%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%5Cright%20%29)
Applying condition: y'(0)=0, we get ![0=\frac{-1}{2}+\frac{\sqrt{3}}{2}c_2\Rightarrow c_2=\frac{1}{\sqrt{3}}](https://tex.z-dn.net/?f=0%3D%5Cfrac%7B-1%7D%7B2%7D%2B%5Cfrac%7B%5Csqrt%7B3%7D%7D%7B2%7Dc_2%5CRightarrow%20c_2%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D)
Therefore,
![y=e^{\frac{-t}{2}}\left ( \cos\left ( \frac{\sqrt{3}t}{2} \right )+\frac{1}{\sqrt{3}}\sin \left ( \frac{\sqrt{3}t}{2} \right ) \right )](https://tex.z-dn.net/?f=y%3De%5E%7B%5Cfrac%7B-t%7D%7B2%7D%7D%5Cleft%20%28%20%5Ccos%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%2B%5Cfrac%7B1%7D%7B%5Csqrt%7B3%7D%7D%5Csin%20%5Cleft%20%28%20%5Cfrac%7B%5Csqrt%7B3%7Dt%7D%7B2%7D%20%5Cright%20%29%20%5Cright%20%29)